Candida tricuspid endocarditis in a non-addict - (:unkn) unknown (Springer New York, 2001)
Isolated native non-rheumatic fungal tricuspid valve endocarditis is rarely described in the absence of intravenous drug addiction or use of intracardiac catheters or concomitant cardiac anomalies. Herein, we report a case of tricuspid valve endocarditis in a non-addict, which was successfully treated with valve replacement. The cultures of blood and vegetations revealed Candida Pichia Etschelsii. Candida tricuspid endocarditis must be considered in any patient with tricuspid vegetation, regardless of predisposing factors.